Outcomes of pediatric patients with oncologic disease or following hematopoietic stem cell transplant supported on extracorporeal membrane oxygenation: The PEDECOR experience. Issue 10 (9th June 2020) - Steppan, Diana A.; Coleman, Ryan D.; Viamonte, Heather K.; Hanson, Sheila J.; Carroll, Megan K.; Klein, Orly R.; Cooke, Kenneth R.; Spinella, Philip C.; Steiner, Marie E.; Loftis, Laura L.; Bembea, Melania M.; ,
Abstract: Background: Outcomes for patients with oncologic disease and/or after hematopoietic stem cell transplant (HSCT) requiring intensive care unit admission have improved, but indications for and outcomes after extracorporeal membrane oxygenation (ECMO) support in this population are poorly characterized. Procedure: We analyzed data from consecutive patients < 18 years with oncologic disease and/or after HSCT reported to a pediatric ECMO registry by nine pediatric centers in the United States between 2011 and 2018. Results: We identified 18 ECMO patients with oncologic disease and/or HSCT, and 415 ECMO controls matched with a propensity score algorithm based on age, gender, race, severity of illness at admission, and reason for ECMO. The primary indication for ECMO was respiratory failure in 66.7% in the oncologic disease and/or HSCT group, and in 70.7% in the matched ECMO control group. Eleven of 18 patients survived to hospital discharge (61.1%), similar to the matched control group (60.8%), P  = 0.979. Children with oncologic disease and/or HSCT had lower mean platelet counts during ECMO and received higher volumes of platelets compared with the control group, mean 14.6 mL/kg/day (standard deviations [SD], 9.8) versus mean 9.3 mL/kg/day (SD, 10.4), P  = 0.001. Of the 11 surviving children with oncologic disease and/or HSCT, five sustained new neurologic disorders (45.5%) versus 45 of 222 (20.3%) in the control group, P  = 0.061. Bleeding complications were similar in the two groups. Conclusions: Outcomes of patients with oncologic disease and/or HSCT supported on ECMO in the current era are not significantly different compared with matched ECMO controls and are improved from previously published reports.